Functional nanomaterials through esterification of cellulose: a review of chemistry and application - Wang, Yonggui; Wang, Xiaojie; Xie, Yanjun; Zhang, Kai (Cellulose (London), 2018)
As the most abundant biopolymer in nature, cellulose has become a fascinating building block for the design of functional nanomaterials. Owing to the presence of numerous hydroxyl groups, cellulose provides a unique platform for the preparation of new materials via versatile chemical modifications. This critical review aims to present the advances about nanomaterials based on cellulose derivatives with the focus on cellulose esters within the last two decades, including the chemistry and application of these nanostructured materials. This review starts with the introduction on first fundamental aspects about diverse esterification techniques used up to now to modify cellulose. The in situ esterification for the isolation of nanocelluloses and diverse post esterification methods of nanocelluloses for the surface functionalization were highlighted in the following description. Various esterification strategies and further nanostructure constructions have been developed aiming to confer specific properties to cellulose esters, extending therefore their feasibility for highly sophisticated applications, which were summarized with respect to the categories of the introduced ester moieties. Thus, this review assembles and emphasizes the state-of-art knowledge of functional nanomaterials derived from diverse esterified cellulose compounds.